Use of open education resources by library and information studies students in Universities in Ibadan, Oyo State, Nigeria (2025)
The use of open educational resources by Library and Information Science (LIS) undergraduates can enhance their learning and research activities. However, findings from studies have revealed that some of the LIS undergraduates are not taking advantage of these resources. This could be a function of information retrieval skills. Thus, this study examined the use of open educational resources by library and information studies students in two universities in Ibadan, Oyo State, Nigeria. A descriptive survey research design of the correlational type was used for the study. The population consisted of LIS undergraduates in Universities in Ibadan. A simple random sampling technique was used to arrive at a sample size of 143. The questionnaire was the instrument used for data collection. Data was analysed using descriptive statistics. The Statistical Package for the Social Sciences (SPSS) was used to interpret the results. Findings show that challenges affecting the use of open educational resources by most of the respondents include a lack of orientation regarding the availability of open educational resources. The study recommends that lecturers and management of library schools should encourage the use of these resources and provide relevant training for their effective use.